A qualitative exploration of families' experiences and resilience factors during the COVID-19 pandemic. (May 2022) - Carney, Jessica R; Behrens, Brigid; Miller-Graff, Laura E
The COVID-19 pandemic has prompted widespread changes and challenges worldwide. In the context of the early months of the pandemic, the current study utilized thematic analysis to assess parents' ( N = 13) perspectives of need for resources to foster their family's wellbeing. Five themes emerged: Information Deficits, Need for More Instrumental Supports, Frustration and Worry, Resources Promoting Resilience, and Positive Perspective Shift. Results indicate the importance of information and expanded access to community resources to scaffold resilience in the face of ongoing mass stressors.